Clarifying and reframing the neoliberal critique of educational policy using policy process theories. Issue 2 (4th March 2019) - Ertas, Nevbahar; McKnight, Andrew N.
ABSTRACT: This paper explores the vocabulary and frameworks offered by two theories of public policy process: the advocacy coalition framework (ACF) and the narrative policy framework (NPF) and what they offer to the study of global education reform. The foci of ACF are policy subsystems, formation of advocacy coalitions around policy issues, and their impact on policy change; the emphasis of NPF is the divergent narratives developed and used by these coalitions. This paper reviews each theoretical framework, summarizes existing research literature on their education policy applications, and then poses alternative questions and suggest alternatives to study global education policies, especially those presently critiqued using the term neoliberal which we position as nebulous in its current usage. The aim is to open channels of communication for scholars from different disciplines by introducing different theoretical approaches to analyse the role of the numerous elements that shape global education policy.